Oogonial proliferation and early oocyte dynamics during the reproductive cycle of two Clupeiform fish species. Issue 1 (17th October 2022) - Charitonidou, Katerina; Panteris, Emmanuel; Ganias, Kostas
Abstract: Although oogonial proliferation continues in mature females in most teleosts, its dynamics and the transformation of oogonia to early meiotic oocytes during the reproductive cycle have received little attention. In the present study, early oogenesis was examined throughout the reproductive cycle in two Clupeiform fishes, the Mediterranean sardine, Sardina pilchardus, and the European anchovy, Engraulis encrasicolus . Observations using confocal laser scanning microscopy (CLSM) provided extensive information on markers of oogonial proliferation (mitotic divisions, oogonia nests) and meiotic prophase I divisions of oocyte nests (leptotene, zygotene, pachytene, diplotene) in ovaries of different reproductive phases. In sardine, oogonial proliferation persisted throughout the entire reproductive cycle, whereas in anchovy, it was more pronounced prior to (developing ovaries) and after (resting ovaries) the spawning period. Anchovy exhibited a higher rate of meiotic activity in developing ovaries, whereas sardine exhibited a higher rate in resting ovaries. The observed differences between the two species can potentially be attributed to different seasonal patterns of energy allocation to reproduction and the synchronization between feeding and the spawning season.